Effects of tofersen treatment in patients with SOD1-ALS in a “real-world” setting - a 12-month multicenter cohort study from the German early access program - Wiesenfarth, Maximilian; Dorst, Johannes; Brenner, David; Elmas, Zeynep; Parlak, Özlem; Uzelac, Zeljko; Kandler, Katharina; Mayer, Kristina; Weiland, Ulrike; Herrmann, Christine; Schuster, Joachim; Freischmidt, Axel; et al. (EClinicalMedicine, 2024)
Background - In April 2023, the antisense oligonucleotide tofersen was approved by the U.S. Food and Drug Administration (FDA) for treatment of SOD1-amyotrophic lateral sclerosis (ALS), after a decrease of neurofilament light chain (NfL) levels had been demonstrated. - Methods - Between 03/2022 and 04/2023, 24 patients with SOD1-ALS from ten German ALS reference centers were followed-up until the cut-off date for ALS functional rating scale revised (ALSFRS-R), progression rate (loss of ALSFRS-R/month), NfL, phosphorylated neurofilament heavy chain (pNfH) in cerebrospinal fluid (CSF), and adverse events. - Findings - During the observation period, median ALSFRS-R decreased from 38.0 (IQR 32.0-42.0) to 35.0 (IQR 29.0-42.0), corresponding to a median progression rate of 0.11 (IQR −0.09 to 0.32) points of ALSFRS-R lost per month. Median serum NfL declined from 78.0 pg/ml (IQR 37.0-147.0 pg/ml; n = 23) to 36.0 pg/ml (IQR 22.0-65.0 pg/ml; n = 23; p = 0.02), median pNfH in CSF from 2226 pg/ml (IQR 1061-6138 pg/ml; n = 18) to 1151 pg/ml (IQR 521-2360 pg/ml; n = 18; p = 0.02). In the CSF, we detected a pleocytosis in 73% of patients (11 of 15) and an intrathecal immunoglobulin synthesis (IgG, IgM, or IgA) in 9 out of 10 patients. Two drug-related serious adverse events were reported. - Interpretation - Consistent with the VALOR study and its Open Label Extension (OLE), our results confirm a reduction of NfL serum levels, and moreover show a reduction of pNfH in CSF. The therapy was safe, as no persistent symptoms were observed. Pleocytosis and Ig synthesis in CSF with clinical symptoms related to myeloradiculitis in two patients, indicate the potential of an autoimmune reaction. - Funding - No funding was received towards this study.